Plant centromeres. (April 2017) - Comai, Luca; Maheshwari, Shamoni; Marimuthu, Mohan P A
Highlights: Rapid evolution of centromere DNA and its determinant CENH3 is enigmatic. Evidence is lacking for specific interaction between CENH3 and centromere DNA. Epigenetic plasticity of centromeres exemplified by the formation of neocentromeres. Neocentromeres can form on single copy DNA, but are eventually invaded by DNA repeats. Epigenetic incompatibility between centromeres results in uniparental missegregation. Abstract : Plant centromeres, which are determined epigenetically by centromeric histone 3 (CENH3) have revealed surprising structural diversity, ranging from the canonical monocentric seen in vertebrates, to polycentric, and holocentric. Normally stable, centromeres can change position over evolutionary times or upon genomic stress, such as when chromosomes are broken. At the DNA level, centromeres can be based on single copy DNA or more commonly on repeats. Rapid evolution of centromeric sequences and of CENH3 protein remains a mystery, as evidence of co-adaptation is lacking. Epigenetic differences between parents can trigger uniparental centromere failure and genome elimination, contributing to postzygotic hybridization barriers.